Clean Dry Dressing, Gauze Betadine And Wound Healing Periodes On Perineum Postpartum Women - Runjati Runjati; Ida Ariyanti; Christina Lia Uripmi (Jurnal Riset Kesehatan, 2012)
This research  aims to find out influence wound care by dry cleand and betadin kassa toward periode recovery time.  The research population waas all postpartum mother that experincing perineum laseration grade II because of episiotomy or spontan laseration. Mann Whithney test was appliend to test inflece wound care by dry clean and betadin kassa toward period of recovery perineum wound. The research result found that means of periode of recovery perineum wound using dry and clean care was 8.30, and median value was 8, means of recovery perineum wound using betadin kassa care was 7,35, and median value was 7. There was decrease means value betwwen dry clean care and betadin kassa care which were 0.95 and p value sebesar 0.001.  result of analysis using mann whithney test found that Asym. Sig is 0, 001 (p value less than 0,05The methode of care using betadin kassa showed shorter periode of time recovery toward perineum wound than dry clean.